Neuroscienze, Scienze Umane e Pedagogia: quale rapporto? Prospettive e limiti delle Neuroscienze - Andrea Peru (Firenze University Press, 2011)
Neuroscience is the field that attempts to link psychological processes to brain activity. Classic neuropsychological approaches and powerful new techniques supported by rigorous methodological procedures enable neuroscientists to reveal the neuronal correlates of mental functions such as talking, reasoning, remembering, imaging, etc. This does not mean, however, that the brain expresses the mind in a rigid, deterministic way. Indeed, brain functioning is strongly modulated by bodily and environmental input, as well as by interaction with other individuals. In a nutshell, mind and brain are conceived as a reciprocally shaped unit which underpins human behaviour.